Suspected severe post‐anaesthetic myopathy or myelopathy in a Clydesdale horse resulting in euthanasia. Issue 3 (21st May 2022) - Lloyd, Ffion; Dixon, Claire; Kropf, Josephine; Bellitto, Nicholas; Murison, Pamela
Abstract: This case report describes suspected myopathy or myelopathy in a 5‐year‐old Clydesdale gelding following general anaesthesia for sarcoid removal. The lowest mean arterial pressure was 67 mmHg. Hyperlactataemia and tachycardia were observed during anaesthesia prompting abortion of surgery. The horse was unable to stand with assistance from a specialised sling. Azotaemia and hyperkalaemia developed in recovery and worsened despite therapeutic interventions. Euthanasia was performed given the grave prognosis. Postmortem examination was not carried out but could have provided a definitive diagnosis. Specific factors have been identified in the prevention of post‐anaesthetic myopathy, including maintenance of adequate tissue perfusion and oxygenation and careful positioning. Potential improvements in the anaesthetic management of this case in relation to these factors are discussed.